LOCAL WISDOM FOR CORAL REEF CONSERVATION IN THE SPERMONDE ISLANDS (International Conference on Social and Islamic Studies, 2022)
The research examines and analyzes the level of local wisdom in preserving coral reefs in the Spermonde Islands community. Specifically, the main research locations are Barrang Caddi Island, Badi Island and Bontosua Island. The choice of location was based on the damaged condition of the coral reef ecosystem, the existence of a coral reef ecosystem rehabilitation program that was implemented involving the community, and even though it was located on small islands, the means of transportation and communication were smooth. The research was conducted from September to November 2022. This research is classified as a quantitative descriptive research with a sample size of 200 heads of families selected using the stratified random sampling method. The results showed that the level of local wisdom in preserving coral reefs was in the high category. Local wisdom in terms of human-nature relations, human-human relations, as well as trust in intra-human relations, is very supportive in preserving coral reefs. Local wisdom includes knowledge of the passimombalang hornbill for the season and fishing area, knowledge of the pa'boyaboyang hornbill for ship repair and fishing gear, Pa'lopian knowledge of the use of wind, currents and waves, as well as natural signs in the sky, sea and land, belief in not catching the fish around the sacred taka-taka, the social structure of the punggawa mustard community, and the prohibition to go out to sea on Fridays which have an impact on the marine ecosystem. These findings support the theory that local wisdom in a place is inseparable from the influence of various factors and influences people's behavior in or towards the environment.